Gender differences in suicide and suicide attempts among US Army soldiers. Issue 3 (28th February 2015) - Maguen, Shira; Skopp, Nancy A.; Zhang, Ying; Smolenski, Derek J.
Abstract: In order to best tailor suicide prevention initiatives and programs, it is critical to gain an understanding of how service members׳ suicide risk factors may differ by gender. We aimed to better understand gender differences in suicide and suicide attempts among soldiers, including demographic, military, mental health, and other risk factors. We also examined risk factors uniquely associated with suicide and suicide attempts. We conducted a retrospective study of 1857 US Army soldiers who died by suicide or attempted suicide between 2008 and 2010 and had a Department of Defense Suicide Event Report. Female and male soldiers had more similarities than differences when examining risk factors associated with suicide. The only gender difference approaching significance was workplace difficulties, which was more strongly associated with suicide for female soldiers, compared to their male counterparts. Among suicide decedents, the most common risk factor was having a failed intimate relationship in the 90 days prior to suicide. Among those who attempted suicide, the most common risk factor was a major psychiatric diagnosis. Better understanding both gender differences and risk factors uniquely associated with suicide has critical prevention and public health implications as we work to better understand preventable mortality in our youngest generation of service members. Highlights: We examined risk factors associated with suicide in male and female soldiers. Female and male soldiers had more risk factor similarities than differences. Workplace difficulties were associated with suicide vs. attempts for females. The most common suicide vs. attempt risk factor was a failed relationship. The most common attempt vs. suicide risk factor was a psychiatric diagnosis.